Recalibration of Beam Evaluation Tool - Marchenko, Alla (2024)
Due to the harsh radiation environment in space the electronic devices may experience malfunction and even damaging effects caused by Single Event Effects. In order to verify the radiation tolerance of the devices, the test must be performed with a radiation beam before the mission. In order to obtain more reliable results of the test, the Beam Evaluation Tool was developed at CNES (BET-C). BET-C is designed to validate the particle energy and the distribution of the beam during the tests. The tool is utilising a position sensitive detector. The system is still under improvement after it was partially modified. Due to modifications, recalibration of the system was in order. Both energy calculation and position distribution had certain inaccuracies which were corrected by determining the calibration functions. The correction functions were established by using the non processed data extracted from the test campaign at UCLouvain where the BET-C system was tested under high energy ion beams. The results obtained with calibration function show considerable improvement in position distribution for all the ions. Regarding the energy, values close to the theoretical ones were achieved by using the data extracted from measurements with aluminium, chromium, nickel and rhodium. During measurements with carbon the position distribution was not detected and the raw signal that was obtained was too weak to include Carbon in the calibration. With xenon the upper limit of detection was reached leading to the conclusion that the optimal energy range for detection is between 250 MeV and 995 MeV.